Effect of constant immigration in plant–pathogen–herbivore interactions - Mukherjee, Debasis (Mathematics and computers in simulation, 2019)
This paper presents a model for plants subject to a disease, harvested by (insect) herbivores and it also includes natural enemies of the latter. Basic results on boundedness, feasibility of equilibria, uniform persistence and local and global stability issues are investigated. Numerical simulations are carried out in order to validate the applicability of the model under consideration.